Corrosion mitigation of steel rebars in chloride contaminated concrete pore solution using inhibitor: An electrochemical investigation. (10th June 2018) - Lee, Han-Seung; Yang, Hyun-Min; Singh, Jitendra Kumar; Prasad, Shailesh Kumar; Yoo, Bongyoung
Highlights: The prepared inhibitor has worked effectively to reduce the corrosion of steel. Synthesized inhibitor work as anodic inhibitor. High concentration of inhibitor is required to mitigate the corrosion of steel. 96% efficiency was found for 5 v/v% inhibitor after 1 h of exposure. Abstract: Inhibitor is one of the most accepted method to reduce, prolong the initiation of steel corrosion and increase the threshold value of Cl − and CO3 2− ions. In present study, we have mixed sodium salt of phosphate and benzoate along with benzo triazole in water to prepare the inhibitor. Open circuit potential (OCP) results show that 5 v/v% inhibitor was exhibited most positive (nobler) potential than others at its prolonged exposure in simulated concrete pore (SCP) + 3.5 wt% NaCl solution. The OCP of 3 and 5% inhibitor containing solution proved that these concentrations are away from under corrosion region of steel rebar even after 192 h of exposure in SCP + 3.5 wt% NaCl solution. Electrochemical impedance spectroscopy (EIS) results show that the charge transfers resistance (Rct ) to be highest for 5% inhibitor and gradually decreased once the concentration was reduced with exposure periods. Potentiodynamic studies reveal that inhibitor shows passive properties due to adsorption of inhibitor molecules on steel surface and enhance the corrosion resistance properties. The efficiency was calculated using Rct and corrosion current density (Icorr ) process and found that 3 and 5% inhibitor exhibit around 89 and 96%, respectively after 1 h of exposure in SCP + 3.5 wt% NaCl solution.